The Emerging Roles of the RNA Binding Protein QKI in Cardiovascular Development and Function - Chen, Xinyun; Yin, Jianwen; Cao, Dayan; Xiao, Deyong; Zhou, Zhongjun; Liu, Ying; Shou, Weinian (Frontiers in Cell and Developmental Biology, 2021)
RNA binding proteins (RBPs) have a broad biological and physiological function and are critical in regulating pre-mRNA posttranscriptional processing, intracellular migration, and mRNA stability. QKI, also known as Quaking, is a member of the signal transduction and activation of RNA (STAR) family, which belongs to the hnRNP K-homology domain protein family. There are three major alternatively spliced isoforms, QKI-5, QKI-6, and QKI-7, differing in C-terminal domains. They share a common RNA binding property, but each isoform can regulate pre-mRNA splicing, transportation, or stability differently in a unique cell type-specific manner. Previously, QKI has drawn great attention for its important disease-causing contribution to various well-known human diseases, especially neurological disorders. A series of recent work has further demonstrated that QKI has important roles in much broader biological systems, such as cardiovascular development, monocyte to macrophage differentiation, bone metabolism, and cancer progression. In this mini-review, we will focus on the emerging roles of QKI in regulating cardiovascular development and function and its potential link to cardiovascular pathophysiology.